A Biocompatible Liquid Pillar[n]arene-Based Drug Reservoir for Topical Drug Delivery - Yahan Zhang; Mengke Ma; Longming Chen; Xinbei Du; Zhao Meng; Han Zhang; Zhibing Zheng; Junyi Chen; Qingbin Meng (MDPI AG, 2022)
Advanced external preparations that possess a sustained-release effect and integrate few irritant elements are urgently needed to satisfy the special requirements of topical administration in the clinic. Here, a series of liquid pillar[n]arene-bearing varying-length oligoethylene oxide chains (OEPns) were designed and synthesized. Following rheological property and biocompatibility investigations, pillar[6]arene with triethylene oxide substituents (TEP6) with satisfactory cavity size were screened as optimal candidate compounds. Then, a supramolecular liquid reservoir was constructed from host-guest complexes between TEP6 and econazole nitrate (ECN), an external antimicrobial agent without additional solvents. In vitro drug-release studies revealed that complexation by TEP6 could regulate the release rate of ECN and afford effective cumulative amounts. In vivo pharmacodynamic studies confirmed the formation of a supramolecular liquid reservoir contributed to the accelerated healing rate of a S. aureus-infected mouse wound model. Overall, these findings have provided the first insights into the construction of a supramolecular liquid reservoir for topical administration.